RISK FACTORS, THE COURSE OF PREGNANCY AND GESTATIONAL OUTCOMES IN DIFFERENT STAGES OF PREGNANCY IN PRETERM BIRTH - Лариса Владимировна Куклина; Елена Николаевна Кравченко; Наталья Витальевна Батырева; Светлана Николаевна Гринь; Ольга Александровна Марковская (The Publishing House Medicine and Enlightenment, 2021)
The aim of the research - to evaluate risk factors, features of the course of pregnancy, childbirth and outcomes for newborns in very early preterm birth and preterm birth in the gestation period from 28 to 36 weeks 6 days. Materials and methods. The first main group (n = 66) included patients with very early preterm birth (VEPB), the second main group (n = 84) consisted of patients with preterm birth in pregnancy from 28 to 36 weeks 6 days of pregnancy. The control group (n = 50) included pregnant women who gave birth on time. Results. In the first main group, the age of women was 31.2 ± 1.3 years, in the second main group - 27.3 ± 1.1 years, and in the control group - 24.3 ± 1.5 years. Obstetric anamnesis in the first main group was burdened in 80.3 % of patients, in the second main group in 69 % and in the control group in 46 % (рI-К < 0.001 и рII-К = 0.009) of pregnant women. Of the gynecological diseases detected during pregnancy, bacterial vaginosis prevailed in women of the I and II main groups (39.4 % and 36.9 %, respectively), non-specific vaginitis (21.2 % and 22.6 %), in the control group - in 12 % (p = 0.002) and 8 % (pI-К = 0.049, pII-К = 0.030), respectively. In VEPB, in 31.8 % of cases, the delivery was completed by caesarean section, the indications for operative delivery were: bleeding associated with placental abruption and presentation (n = 8); prenatal discharge of amniotic fluid with an incorrect fetal position (n = 4); preeclampsia (n = 7); decompensated placental insufficiency (n = 1); loss of umbilical cord loops (n = 1). Conclusion. The results of the study showed that a significant impact on the level of very early preterm birth has: complicated obstetric and gynecological history (p < 0.001), kidney disease (p = 0.009), anemia (p = 0.006), genital infections (p = 0.030), viral infections during pregnancy (p = 0.034). The structure of gestational complications was dominated by placental insufficiency (p < 0.001), recurrent threat of termination of pregnancy (p = 0.021), and preeclampsia (p < 0.001).